Analysis of the population dynamics in the “Slavic World” with a special focus on Russia - Nina N. Loginova; Milan M. Radovanović; Anatoliy A. Yamashkin; Goran Vasin; Marko D. Petrović; Dunja Demirović Bajrami (Faculty of Geography, Universitas Gadjah Mada, 2020)
Population changes of the Russians and other Slavs are an important original indicator of demographic, economic, political, and cultural analysis of over 300 million Slavic inhabitants in Central, Eastern, and Southeastern Europe. The indicators are conditioned by the large number of people executed in World War I and World War II, significant economic migrations, the disintegration of the Soviet Union, Yugoslavia, and Czechoslovakia. Utilizing data from official reports, the authors proceed to analyze the demographic tendencies in order to find out the relationship between modern demographic trends and political and economic events over the past years. The results showed that economic and demographic stagnation, which favor religious and national (ethnic) ambivalence, influence the strengthening of groups ethnically isolated or religiously differentiated in the observed macroregions of Eurasia. The contemporary challenges of modern society in terms of global politics (e.g. terrorism and migrations) will be more pronounced and turbulent in these areas. For these reasons, the original data represent an important segment of the study of Slavic history, demography, and politics throughout the turbulent 20th century and the beginning of the new millennium.